2012
DOI: 10.9790/0837-0550112
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Management and the Manufacturing Sector Performance in the Nigerian Economy

Abstract: Since Nigeria is heavily factor-input import dependent, the inability to locally source the required inputs in the manufacturing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…Bleaney and Vargas (2009) also find evidence that, in emerging markets, currency devaluation depresses economic growth. Similar results are reported by Munthali et al (2010), Ehinomen et al (2012), Gylfason and Radetzki (1991), Choudhary and Chaudhry (2007), Blecker and Razmi (2008), Munthali et al (2010), Ehinomen et al (2012), Shahbaz, Islam, and Aamir (2012), Bahmani-Oskooee and Abera Gelan (2013) and Ilir (2006). These studies generally find that devaluations result in contractionary effects on economic growth in developing countries.…”
Section: Literature Reviewsupporting
confidence: 87%
“…Bleaney and Vargas (2009) also find evidence that, in emerging markets, currency devaluation depresses economic growth. Similar results are reported by Munthali et al (2010), Ehinomen et al (2012), Gylfason and Radetzki (1991), Choudhary and Chaudhry (2007), Blecker and Razmi (2008), Munthali et al (2010), Ehinomen et al (2012), Shahbaz, Islam, and Aamir (2012), Bahmani-Oskooee and Abera Gelan (2013) and Ilir (2006). These studies generally find that devaluations result in contractionary effects on economic growth in developing countries.…”
Section: Literature Reviewsupporting
confidence: 87%
“…A previous study mentioned that more than 18 percent of the household had increased their real income 2 to 3 times after five years of engagement in palm oil cultivation (Budidarsono et al, 2012). The manufacturing industries can create employment, which helps boost agriculture and diversify the economy to increase its foreign exchange earnings (Ehinomen, 2012). Figure 3 shows the location of palm oil plantations per province in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…He pointed out that regardless of the alternative measures, the actual exchange rate misalignment and fluctuations will have an adverse impact on the growth of Nigeria's non-oil exports. Ehinomen and Oladipo (2012) studied the impact of exchange rate management on manufacturing growth in Nigeria and arrived at a seemingly perverse finding. By using ordinary least squares (OLS) multiple regression analysis and time series data over the period 1986 to 2010, the empirical results of the study indicated that exchange rate depreciation was part of the 1986 Structural Adjustment Policy (SAP), in which there was no significant relationship with the manufacturing industry's productivity during that period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the empirical evidence, Ehinomen and Oladipo (2012) suggested that the government should guide its exchange rate management policy in order to boost exchange rate appreciation and further condense the cost of production in the manufacturing sector that depends heavily on foreign inputs, while there should be simultaneously a total ban on the importation of consumer and intermediate goods that can be or are manufactured locally.…”
Section: Literature Reviewmentioning
confidence: 99%